1990
DOI: 10.1126/science.2218526
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Human Psychological Differences: The Minnesota Study of Twins Reared Apart

Abstract: Since 1979, a continuing study of monozygotic and dizygotic twins, separated in infancy and reared apart, has subjected more than 100 sets of reared-apart twins or triplets to a week of intensive psychological and physiological assessment. Like the prior, smaller studies of monozygotic twins reared apart, about 70% of the variance in IQ was found to be associated with genetic variation. On multiple measures of personality and temperament, occupational and leisure-time interests, and social attitudes, monozygot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
515
2
19

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,210 publications
(550 citation statements)
references
References 46 publications
14
515
2
19
Order By: Relevance
“…For (z-parameters, enough evidence seems to exist to conclude that genetic factors contribute significantly to variations in c~-amplitude and c~-index. The high concordance in MZ twins is also seen in MZ twins reared apart (Bouchard et al 1990), suggesting that common environmental variance is not an important factor. Use of spectral analysis of the EEG has led to high heritabilities being shown for various frequency bands.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…For (z-parameters, enough evidence seems to exist to conclude that genetic factors contribute significantly to variations in c~-amplitude and c~-index. The high concordance in MZ twins is also seen in MZ twins reared apart (Bouchard et al 1990), suggesting that common environmental variance is not an important factor. Use of spectral analysis of the EEG has led to high heritabilities being shown for various frequency bands.…”
Section: Resultsmentioning
confidence: 93%
“…This is slightly less than a person resembles himself over time. With the same procedure, Stassen et al (1988a, b) analyzed EEGs of MZ and DZ twins reared apart (Bouchard et al 1990). The previous results were confirmed; the similarity of MZ spectral patterns is only slightly less than that of the same subject compared with himself over time, and the average similarity of the DZ pairs differs significantly from the similarity of a group of UR individuals.…”
Section: Genetics Of Eeg Powers As Defined By Spectral Analysis Technmentioning
confidence: 99%
“…The validity of this approach is bolstered by evidence that the majority of personality traits appear to be moderately to highly heritable, with only minor influences of individual environment in twins reared apart. 10,11 Following the Cloninger model, much of this work has focused on candidate genes affecting monoaminergic neurotransmission and their prediction of variation in temperament ratings on instruments such as the TPQ. However, even for the most widely studied such gene, a promoter variant in the serotonin transporter (5-HTTLPR), a consistent picture has not emerged.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Twins, family and adoptive studies have shown that at least 50-79% of the blood pressure variation in humans can be attributed to genetic factors. 6,7 Compared to the offspring of two normotensive parents, blood pressure is higher in the offspring of one normotensive and one hypertensive parent, and highest in the offspring of two hypertensive parents. 8 These distributions are evident in infancy and persists through late adulthood.…”
Section: Introductionmentioning
confidence: 99%